2020
DOI: 10.3390/plants9030357
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Essential Oils (CEOs) and Their Applications in Food: An Overview

Abstract: Citrus is a genus belonging to the Rutaceae family and includes important crops like orange, lemons, pummelos, grapefruits, limes, etc. Citrus essential oils (CEOs) consist of some major biologically active compounds like α-/β-pinene, sabinene, β-myrcene, d-limonene, linalool, α-humulene, and α-terpineol belonging to the monoterpenes, monoterpene aldehyde/alcohol, and sesquiterpenes group, respectively. These compounds possess several health beneficial properties like antioxidant, anti-inflammatory, anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(141 citation statements)
references
References 170 publications
2
138
0
1
Order By: Relevance
“…The results demonstrated that the most abundant constituent in both the essential oil and hydrosol was linalool ( Table 1 ). Linalool is a terpenoid that is commonly present in plants, such as citrus [ 7 ]. It is known that linalool possesses several bioactivities, such as antibacterial [ 8 ], antiviral [ 9 ], antifungal [ 10 ], anti-inflammatory, and anticancer properties [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the most abundant constituent in both the essential oil and hydrosol was linalool ( Table 1 ). Linalool is a terpenoid that is commonly present in plants, such as citrus [ 7 ]. It is known that linalool possesses several bioactivities, such as antibacterial [ 8 ], antiviral [ 9 ], antifungal [ 10 ], anti-inflammatory, and anticancer properties [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Citrus EOs have been extensively studied for their potential applications in food packaging. There are numerous scientific reports dealing with the development of materials for active food packaging, containing EOs that serve as the active components [ 16 , 17 ]. These food packaging systems are designed mainly to protect the food from environmental conditions, like humidity, light, and temperature, along with other factors like dust, microorganisms, and mechanical deformation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the CEOs, the bergamot essential oil and its terpene showed the best antibacterial action (against 7 out of 11 strains), followed by lemon EO (5 out of 11 strains), and bitter orange (4 out of 11 strains). Bora et al (2020) and Pandey et al (2017) [2,15] highlighted that CEOs, thanks to their antimicrobial properties, could be used in the food industry. In fact, the antimicrobial activity of CEOs against human pathogenic bacteria has been reported from several authors [5,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…The Citrus species, widely used in the preparation of food, both sweet and savory, are spread all over the world but originally coming from Northern India, Northern Myanmar, Southern China, and Southeast Asia [1]. The citrus genus, and subsequently, the Citrus fruits have many compounds that give them unique flavor and aroma and that have beneficial effects on health, such as phenols, flavonoids, limonoids, essential oils (EOs), and vitamins, particularly, vitamin C and carotenoids [2]. Citrus essential oils (CEOs) are extracted and extensively studied for their potential uses in the food industry [3].…”
Section: Introductionmentioning
confidence: 99%